Efisiensi Belanja Pemerintah Daerah dan Dampaknya Terhadap Pertumbuhan Ekonomi Daerah Tahun 2004-2013 - Andriani, Tety; Mahi, Bernadictus Raksaka (UI Scholars Hub, 2015)
Fiscal decentralization in Indonesia is expected to improve efficiency of local government and further drive economic growth in the regions. This research studies correlation between the efficiency of the local government expenditure and the economic growth in West Java and North Sumatera. The analysis is divided into two stages. First, expenditure efficiency is measured by using Data Envelopment Analysis (DEA) method. In the second stage, regression analysis is conducted to estimate impacts of the local governments’ efficiency scores and other determinants on the regional economic growth. The research result shows that, in West Java and North Sumatera, the local government expenditure efficiency scores have positive and significant correlation with the economic growth in the region. Hence, the bigger the efficiency scores of the regional government expenditure, the higher the economic growth in the region.